2012
DOI: 10.1007/s00705-012-1449-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage vB_EcoM_FV3: a new member of “rV5-like viruses”

Abstract: A proposed new genus of the family Myoviridae, "rV5-like viruses", includes two lytic bacteriophages: Escherichia coli O157: H7-specific bacteriophage rV5 and Salmonella phage PVP-SE1. Here, we present basic properties and genomic characterization of a novel rV5-like phage, vB_EcoM_FV3, which infects E. coli K-12-derived laboratory strains and replicates at high temperature (up to 47 °C). The 136,947-bp genome of vB_EcoM_FV3 contains 218 open reading frames and encodes 5 tRNAs. The genomic content and organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Their closest homologue based on BLAST searches is phage vB_EcoM_FFH2, but there are striking differences in the tail fiber genes, and genes encoding DNA modifying enzymes present in vB_EcoM_FFH2, are absent from C203/P206. These genes, as shown by BLAST searches, are rather similar to those found in the Salmonella phages slur12 and slur16 (Smith et al, 2015), the phage EcoM_FV3 (Truncaite et al, 2012) and Murica (Wilder et al, 2015). It has to be noted that the Mauve alignment of rV5-like genomes indicated that the order of genes is generally uniform in rV5 phages, with sequence shifts responsible for different organizations (Figure 2).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Their closest homologue based on BLAST searches is phage vB_EcoM_FFH2, but there are striking differences in the tail fiber genes, and genes encoding DNA modifying enzymes present in vB_EcoM_FFH2, are absent from C203/P206. These genes, as shown by BLAST searches, are rather similar to those found in the Salmonella phages slur12 and slur16 (Smith et al, 2015), the phage EcoM_FV3 (Truncaite et al, 2012) and Murica (Wilder et al, 2015). It has to be noted that the Mauve alignment of rV5-like genomes indicated that the order of genes is generally uniform in rV5 phages, with sequence shifts responsible for different organizations (Figure 2).…”
Section: Discussionsupporting
confidence: 53%
“…In the recent years, rV5-like phages have been established as a 'singleton' genus within the Myoviridae family, showing similar genomic organization and phenotypic characteristics to each other, but exhibiting significant differences to other coliphages (Smith et al, 2015;Truncaite et al, 2012). Based on their morphology, all of them are members of the Myoviridae family, and phage C203 and P206 are no exception from this notion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these characteristics, phage isolates were classified under the order Caudovirales and Myoviridae family (27). Moreover, these characteristics were similar to those of T1-7-like E. coli phages (4,36). Given the fact that the Myoviridae family contains doublestranded DNA phages (4), all eight phages were presumptively classified under linear double-stranded DNA phages.…”
Section: Discussionmentioning
confidence: 99%
“…70%) of its genes were ORFans [67,68]. Since then five other phages have been reported to be rV5-like: coliphages vB_EcoM-FV3 [69], phAPEC8 [70] and phi92 [59], Cronobacter sakazakii phage vB_CsaM_GAP31 [71] and Salmonella phage PVP-SE1 [39]. To this list we can also add Salmonella phage SSE-121 (JX181824); and, coliphage Delta Y that Andrey Letarov and Alla Golomidova (Winogradsky Institute of Microbiology, RAS, Moscow, Russia), isolated from horse manure, and partially sequenced.…”
Section: Discussionmentioning
confidence: 99%